Smart measurement of water quality parameters and monitoring fish health - Talukder, Ali Ahmed Rezvee; Iqbal, Syed Wasi; Shakil, Mohammad; Khan, Md. Imran (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021